Deep Reinforcement Learning with Adaptive Update Target Combination. (15th August 2019) - Xu, Z; Cao, L; Chen, X
Abstract: Simple and efficient exploration remains a core challenge in deep reinforcement learning. While many exploration methods can be applied to high-dimensional tasks, these methods manually adjust exploration parameters according to domain knowledge. This paper proposes a novel method that can automatically balance exploration and exploitation, as well as combine on-policy and off-policy update targets through a dynamic weighted way based on value difference. The proposed method does not directly affect the probability of a selected action but utilizes the value difference produced during the learning process to adjust update target for guiding the direction of agent's learning. We demonstrate the performance of the proposed method on CartPole-v1, MountainCar-v0, and LunarLander-v2 classic control tasks from the OpenAI Gym. Empirical evaluation results show that by integrating on-policy and off-policy update targets dynamically, this method exhibits superior performance and stability than does the exclusive use of the update target.